2023
DOI: 10.1002/jsfa.12938
|View full text |Cite
|
Sign up to set email alerts
|

Dietary collagen peptide‐chelated trace elements supplementation for breeder hens improves the intestinal health of chick offspring

Yongfa Liu,
Simeng Li,
Zhenwu Huang
et al.

Abstract: BackgroundDietary supplementation with trace elements zinc (Zn), iron (Fe), and manganese (Mn) could promote intestinal development and improve intestinal health. There are, however, few studies examining the possibility that maternal original Zn, Fe, and Mn could regulate the intestinal development and barrier function in the offspring. This study aimed to investigate how the intestinal growth and barrier function of breeder offspring were affected by collagen peptide chelated trace elements (PTE, Zn, Fe, Mn)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…With the prohibition of growth-promoting antibiotics in feed, there is a growing interest to find new alternatives from the perspective of maternal nutrition ( Gao et al., 2023 ; Liu et al., 2024 ). Growing evidence has shown that the growth performance of offspring can be improved by maternal supplementation with plant flavonoids, including genistein, daizein and quercetin ( Amevor et al., 2022 ; Fan et al., 2018 ; Lv et al., 2018a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…With the prohibition of growth-promoting antibiotics in feed, there is a growing interest to find new alternatives from the perspective of maternal nutrition ( Gao et al., 2023 ; Liu et al., 2024 ). Growing evidence has shown that the growth performance of offspring can be improved by maternal supplementation with plant flavonoids, including genistein, daizein and quercetin ( Amevor et al., 2022 ; Fan et al., 2018 ; Lv et al., 2018a , b ).…”
Section: Introductionmentioning
confidence: 99%